The Influence of Institutional Ownership, Managerial Ownership, Independent Board of Commissioners, and Firm Size on Earnings Management in Indonesian Banking Companies (2021–2024) - Wafa Rahma Hidayah; Ati Sumiati; Sri Zulaihati (RTTM, 2025)
This research investigates how institutional ownership, managerial ownership, board of independent commissioners, and firm size influence earnings management among IDX-listed banks in the post-pandemic recovery period (2021-2024). Through simple random sampling techniques, 19 companies obtained a total of 76 observations. The data analysis used panel data regression with a fixed effect model approach through EViews 12 software. The research findings reveal that institutional ownership, managerial ownership, and firm size have positive and significant effects on earnings management, while independent boards of commissioners do not affect earnings management. However, together, all independent variables are proven to affect earnings management.